2005
DOI: 10.1016/j.biortech.2004.05.017
|View full text |Cite
|
Sign up to set email alerts
|

SELCO-Ecopurin® pig slurry treatment system

Abstract: As the practice of intensive animal production increases, there is a need for affordable treatment technologies that can help manage the large amounts of manure generated. Our approach has been to develop an efficient liquid-solid separation module using polymer technology and integrate this separation module into systems of treatment technologies for both the separated liquid and solids. We describe the progress that has been made in management techniques and new technological alternatives for manure treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 1 publication
0
19
0
2
Order By: Relevance
“…As a consequence, in many regions with intensive breeding practices, there are not always enough cultivated fields close to the farm facility, thus transport costs increase and there is a need for onsite pig manure. Aerobic treatment aiming for nitrification and denitrification is a conventional treatment technology applied to liquid fraction (LF) of pig manure (Martinez-Almela and Barrera, 2005;Borin et al, 2013) but its high cost and certain unresolved operating problems do not eliminate the need for a low cost and sustainable cleaner technologies, in line with the European waste management hierarchy. With the aim of facilitating the direct LF re-use and nutrient recycling, different composting approaches for LF have been proposed (Li et al, 2008;Barrena et al, 2011;Bustamante et al, 2013;Vázquez et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…As a consequence, in many regions with intensive breeding practices, there are not always enough cultivated fields close to the farm facility, thus transport costs increase and there is a need for onsite pig manure. Aerobic treatment aiming for nitrification and denitrification is a conventional treatment technology applied to liquid fraction (LF) of pig manure (Martinez-Almela and Barrera, 2005;Borin et al, 2013) but its high cost and certain unresolved operating problems do not eliminate the need for a low cost and sustainable cleaner technologies, in line with the European waste management hierarchy. With the aim of facilitating the direct LF re-use and nutrient recycling, different composting approaches for LF have been proposed (Li et al, 2008;Barrena et al, 2011;Bustamante et al, 2013;Vázquez et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…However, usually only the separated solid fraction (SF) of pig manure is subjected to composting (Bernal et al, 2009;Cerutti et al, 2011;Thu et al, 2012). Depending on their characteristics, SF may be composted without amendment and bulking materials or by mixing with different materials at several ratios ranging from 3:1 to 1:3 SF: amendment (Martinez-Almela and Barrera, 2005;Huang et al 2006;Ros et al, 2006). Nolan et al (2011) found that the addition of a bulking agent (4:1 mass ratio SF: bulking agent) and initial water content below 60% were necessary for composting pig manure SF at a low initial carbon (C) to nitrogen (N) ratio in enclosed vessels.…”
Section: Introductionmentioning
confidence: 99%
“…The SM fraction can be transported off-farm, composted with other organic material, and used as a soil amendment. The LM fraction has lower concentrations of nutrients and pollutants as compared with the SM fraction and can be discharged into water systems after a treatment process such as anaerobic digestion (Martinez-Almela and Barrera 2005). Since the LM fraction has a low C/N ratio and nutrients contained are more readily available as compared with the SM fraction, use of the LM fraction as a fertilizer is now being accepted as an alternative to wastewater treatment (Sánchez and González 2005;Sørensen and Thomsen 2005).…”
Section: Introductionmentioning
confidence: 98%
“…The flocculant polymer allows the aggregation of small (<0.5-1 mm) suspended particles contained in the effluent, increasing the separation efficiency to >90% (Martinez-Almela and Barrera, 2005) and the amount of materials available for the solids handling processes. Then, the obtained mix was mechanically conveyed to the rotary screen with 0.2 mm openings and then to the filter press to further dewater the separated solid fraction.…”
mentioning
confidence: 99%